Food Security On Dryland Farm Households in Selo Sub-District, Boyolali District - Hasanah, Novri Eka Nur; Harianto; Suryana, Achmad (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Population growth has led to an increase in the participation rate of rice consumption. This has led to constant pressure on the limits of food supply. Meanwhile, the uneven distribution of food causes food inequality in local areas. These conditions will cause some regions in Indonesia not to achieve food security, even though food availability is sufficient, if people's food access is not good and food utilization is not in accordance with the rules of balanced and safe nutritious food consumption, then the area cannot be categorized as achieving food security. Drylands have great potential and role in supporting national food availability. Food security at the national or regional level does not automatically guarantee the achievement of food security at the household level.Purpose: This study aims to 1) assess the level of food security of dryland farmer households and 2) analyze the factors affecting the food security of dryland farmer households in the Selo Subdistrict. Design/methodology/approach: Sampling was done by simple random sampling from a sample frame of dryland farmer groups totaling 100 respondents. Household food security was analyzed using the Food Insecurity Experience Scale (FIES) indicator. The factors influencing household food security were analyzed using binary logistic regression. Findings/Result: The prevalence rate of moderate food insecurity is 10.74% of total households in the Selo Subdistrict. Farmer households in the Selo Subdistrict experiencing moderate food insecurity is a serious problem that must be addressed immediately. Although the prevalence rate is relatively small, the actual number is relatively large. The prevalence rate of severe food insecurity in the Selo Subdistrict is 0.00% of total households. The food security status shows that most households in Selo Sub-district fall into the food security category with the majority of households being food producers. Factors that significantly influence the food security status of dryland farming households in the Selo Subdistrict are the length of education of the household head, the number of household members, the ratio of expenditure on rice, and the total household income.Conclusion: The prevalence value of the moderate food insecurity category amounted to 10,74%. The most significant factor is the ratio of household expenditure on rice with an Exp (B) value or odds ratio of 401,150.611. The unstable price of rice has led most households to reduce the amount of rice purchased.Originality/value (State of the art): This study explains that dryland farmer households still have a moderate food insecurity category, although the number is small but must be considered. The rice expenditure ratio is an important factor in influencing food security status which has implications for more optimized government policies. Keywords: binary logistic regression, food security, food insecurity experience scale (fies), household